2020
DOI: 10.1088/1755-1315/468/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of dung beetle (Coleoptera: Scarabaeidae) in oil palm agropasture ecosystem in West Kotawaringin Regency, Central Kalimantan, Indonesia

Abstract: Cattle grazing on oil palm plantation (agropastoral) has the potential to increase biodiversity by providing new habitats and providing foods for invertebrates. Dung beetles use the cattle’s dung for food and to lay eggs. The aim of this research is to study the effect of cattle grazing on oil palm plantation toward the diversity, abundance and ecosystem services of dung beetles. The research was conducted in the oil palm plantation of PT. Astra Agro Lestari Tbk. Central Kalimantan Province. Samplings were don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…The management of oil palm with cattle grazing has a positive impact on the abundance of parasitoids wasp , this is because the regeneration process of crop vegetation continues to increase the diversity of non-crop vegetation. The results of this study are in line with the results found by [17] regarding dung beetles (Coleoptera: Scarabaeidae) and [18] concerning Reduviidae predators that the impact of cattle grazing can increase the abundance of dung beetles and predators of Reduviidae.…”
Section: Resultssupporting
confidence: 91%
“…The management of oil palm with cattle grazing has a positive impact on the abundance of parasitoids wasp , this is because the regeneration process of crop vegetation continues to increase the diversity of non-crop vegetation. The results of this study are in line with the results found by [17] regarding dung beetles (Coleoptera: Scarabaeidae) and [18] concerning Reduviidae predators that the impact of cattle grazing can increase the abundance of dung beetles and predators of Reduviidae.…”
Section: Resultssupporting
confidence: 91%
“…The scarabaeid beetles found in this study were dominated by small body size. The large beetles are more difficult to survive because they require more food and a longer reproductive time (Slade et al 2014;Sa'roni et al 2020).…”
Section: Results and Discussion Abundance Species Richness And Compos...mentioning
confidence: 99%
“…Di Jambi dan Gunung Bwakareang Sulawesi Selatan ditemukan 28 spesies dari famili Cerambycidae dan 37 spesies dari famili Carabidae & Staphylinidae (Atmowidi & Noerdjito, 2016;Qodri et al, 2016). Di perkebunan kelapa sawit, Kalimantan Tengah ditemukan 24 spesies dari famili Scarabaeidae (Sa'roni et al, 2019). Di sungai Membramo Papua ditemukan 29 spesies (Rizal et al, 2019).…”
Section: Pendahuluanunclassified
“…Di perkebunan kelapa sawit, Kalimantan Tengah dan Sungai Mamberamo Papua juga telah ditemukan kekayaan spesies yang lebih tinggi. Secara berurutan, ada 24 dan 28 spesies yang tercatat di kedua lokasi tersebut (Rizal et al, 2019;Sa'roni et al, 2019). Adanya perbedaan kekayaan spesies dari ordo Coleoptera dibandingkan dengan di kawasan lain di Indonesia terkait erat dengan adanya perbedaan kondisi lingkungan, baik secara biologis, fisika maupun kimiawi.…”
Section: Kekayaan Spesies Kumbang Arborealunclassified